Salmonella in eggs: From shopping to consumption—A review providing an evidence‐based analysis of risk factors. Issue 3 (7th May 2021) - Cardoso, Maria João; Nicolau, Anca Ioana; Borda, Daniela; Nielsen, Line; Maia, Rui Leandro; Møretrø, Trond; Ferreira, Vânia; Knøchel, Susanne; Langsrud, Solveig; Teixeira, Paula
Abstract: Nontyphoidal salmonellae are among the most prevalent foodborne pathogens causing gastrointestinal infections worldwide. A high number of cases and outbreaks of salmonellosis are associated with the consumption of eggs and egg products, and several of these occur at the household level. The aim of the current study is to critically evaluate the current status of knowledge on Salmonella in eggs from a consumer's perspective, analyzing the hazard occurrence and the good practices that should be applied to reduce salmonellosis risk. Following a HACCP (Hazard Analysis and Critical Control Point) based approach, some steps along the food journey were identified as Critical Consumer Handling (CCH)—steps in which consumers, through their behavior or choice, can significantly reduce the level of Salmonella in eggs and egg products. From shopping/collecting to consumption, each of these steps is discussed in this review to provide an evidence‐based overview of risk factors of human salmonellosis related to egg consumption. The main message to consumers is to choose Salmonella ‐free eggs (those that some official entity or producer guarantees that does not contain Salmonella ), when available, especially for dishes that are not fully heat treated. Second, as guaranteed Salmonella ‐free eggs are only available in a few countries, refrigerated storage from the point of collection and proper cooking will significantly reduce the risk of salmonellosis. This will require a revision of the actual recommendations/regulations, as not all ensure that eggs are maintained at temperatures that prevent growth of Salmonella from collection until the time of purchasing.